OPTIMIZATION OF DIAGNOSTIC ABDOMINAL GUNSHOT WOUNDS IN COMBAT CONDITIONS - Herasymenko, O.S.; Yenin, R.V.; Shepitko, K.V.; Herasymenko, S.D. (World of Medicine and Biology, 2019)
The purpose of the present study was to optimize the diagnostic scheme for combat abdominal injuries at the II level of medical care by identifying the most informative and fast instrumental diagnostic methods. A clinical and statistical analysis of the results of surgical treatment of 496 wounded with combat abdominal injuries treated in military mobile hospitals from June 2014 to August 2017 was carried out. Additional diagnostic tests were performed to the injured with battle wound of the abdomen in the comparison groups - FAST protocol, laparocentesis and diagnostic laparoscopy. A more frequent FAST protocol for injured with battle wound of the abdomen at level II of medical care in groups 2 and 3 resulted in a decrease in the number of laparocentesis performed from 68.3% (in group 1) to 38.6% (in group 3), and an increase in the number of video laparoscopic studies from 14.9% (in group 1) to 26.6% (in group 3), most of which turned into therapeutic laparoscopy. The data obtained indicate that the widespread introduction of the FAST protocol into the battle wound of the abdomen diagnosis scheme at the II level of medical care helps to reduce the number of invasive (often unfounded) methods, namely, laparocentesis and diagnostic laparotomy, reduce the time spent on diagnosis and the choice of optimal surgical tactics.
Keywords: gunshot wounds of the abdomen; laparocentesis; videolaparoscopy; ultrasound